Supplementation of different sources of selenium on laying performance, egg quality traits, and shell calcification expressions in 50 weeks Lohmann Brown layer hen reproductive tract - Hemly, Nur Izzah Mohd; undefined, undefined; Zainuddin, Nurafiqah Najwa; Muhammad, Aliyu Ibrahim; Chwen, Loh Teck; Samsudin, Anjas Asmara; undefined, undefined; undefined, undefined; undefined, undefined; undefined, undefined (Chiang Mai University, 2023)
Massive consumption and exportation of eggs in Malaysia are possible through improving layer productive performances and egg quality through antioxidant supplementation such as selenium. Preferential supplementation of organic sele-nium in poultry diets was due to its bioavailability. The present study assesses the effects of feeding 50 weeks layer hens with sodium selenite, selenised yeast, and Stenotrophomonas maltophilia, ADS18 as a source of selenium and vitamin E on laying integrity, egg qualities, and reproductive gene expressions. The four different treatments (diets) used in the experiment were tagged as follows: Control: a basal diet containing 100 mg/kg vitamin E, SS: basal diet plus 0.3 mg/kg sodium selenite, Se-yeast: basal diet plus 0.3 mg/kg selenised yeast, and VADS18: basal diet plus 0.3 mg/kg ADS18. Productive performances were analysed throughout a 90-days of production. Eggs were collected biweekly, and egg qualities were measured. The uterine and magnum tissues were examined for the genes ovocleidin and ovocalyxin; OCX32, OCX36, OC17 and OC116. The results showed that Se-yeast significantly (P < 0.05) increased laying integrity, while VADS18 supplementation significantly (P < 0.05) increased egg weight. Supplementation of different selenium sources significantly (P < 0.05) improved egg production and Haugh quality. Additionally, uterine gene expression was significantly (P < 0.05) increased by VADS18 supplementation. Therefore, adding organic selenium to the diet maintained various laying performance indicators, egg qualities, and upregulated gene expression. Further evaluations are required to determine the optimum inclusion level of ADS18 poultry.